(3GdeONd dHMhK GdYedjGJs - (3YHO GdQShd YHO GdQRGb(B, (3GdehShjs ((3YeGf(B:s (3OGQ hGFd ddfTQ(B,s, 2002)
(3JLO aj gPG GdcJGH (B: (3GdHQeLI GdNWjI , Jchjf GdeTcdI hWQjbI GdQSe GdHjGfj ,GdHQeLI GdNWjI ,WQjbI GdSeHdcS JMdjd GdMSGHjI hGdMd GdKfGFj, Gdfbd hGdJNUjU , JMdjd GdbQGQ ,THcGJ GdCYeGd , feGPL GdeNRhf , fXQjI Uaha GdEfJXGQ , fXQjGJ GdeHGQjGJs
Keywords: (3GdHQeLI GdNWjIs; (3HMhKs; (3YedjGJs